2015
DOI: 10.1038/tp.2015.109
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2/3 receptor antagonism reduces activity-based anorexia

Abstract: Anorexia nervosa (AN) is an eating disorder characterized by severe hypophagia and weight loss, and an intense fear of weight gain. Activity-based anorexia (ABA) refers to the weight loss, hypophagia and paradoxical hyperactivity that develops in rodents exposed to running wheels and restricted food access, and provides a model for aspects of AN. The atypical antipsychotic olanzapine was recently shown to reduce both AN symptoms and ABA. We examined which component of the complex pharmacological profile of ola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 78 publications
0
43
1
Order By: Relevance
“…Indeed, mice treated with the SSRI fluoxetine during the ABA paradigm showed increased food intake and reduced FAA; however, survival of the ABA paradigm was not increased compared to vehicle‐treated mice . Furthermore, treatment with d‐fenfluramine, a drug that stimulates 5‐HT release and blocks its reuptake, primarily through the 5‐HT 2C receptor, either did not impact the ABA phenotype or accelerated the associated weight loss and selective 5‐HT receptor antagonism promoted weight loss in ABA . Conversely, decreasing 5‐HT signalling by treatment with the 5‐HT antagonist 8‐OHDPAT was shown to prevent starvation‐induced hyperactivity in ABA without changing food intake .…”
Section: Serotonin Disruptions In Abamentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, mice treated with the SSRI fluoxetine during the ABA paradigm showed increased food intake and reduced FAA; however, survival of the ABA paradigm was not increased compared to vehicle‐treated mice . Furthermore, treatment with d‐fenfluramine, a drug that stimulates 5‐HT release and blocks its reuptake, primarily through the 5‐HT 2C receptor, either did not impact the ABA phenotype or accelerated the associated weight loss and selective 5‐HT receptor antagonism promoted weight loss in ABA . Conversely, decreasing 5‐HT signalling by treatment with the 5‐HT antagonist 8‐OHDPAT was shown to prevent starvation‐induced hyperactivity in ABA without changing food intake .…”
Section: Serotonin Disruptions In Abamentioning
confidence: 99%
“…It may be that the behavioural responses to global DA antagonism differ in the altered reward context of the ABA paradigm. Selective antagonism of DA2/3 receptors is shown to ameliorate ABA by increasing food intake to a greater extent than olanzapine administration, which is an antagonist to 5‐HT2 and DA receptors D1‐5, suggesting that the effects of D2/3 may underlie the mechanism of action of olanzapine in reducing ABA symptoms . Because dopamine is integral to mesolimbic reward processing, it follows logically that central reward dysfunction in AN and ABA is associated with the DA disturbances described above, specifically within the mesolimbic reward circuit.…”
Section: Dopamine and Reward Disruptions In Abamentioning
confidence: 99%
See 1 more Smart Citation
“…Weight gain has been associated with increases in fasting glucose and lipids [57]. Selective anatgonism of D2 receptors with amisulpiride reduced largely severe weight loss and hypophagia in anorexia nervosa patients [58]. To explain the mechanisms of sulpiride-induced overweight, Parada et al [59] reported that intrahypothalamic injections of sulpiride elicited feeding, even in satiated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Brain reward learning is altered in AN, behavior that has been associated with brain dopamine function suggesting that dopaminergic agents could ameliorate this dysfunction [132]. One study that tested serotonin 2A/2C, serotonin 3, dopamine D1-like, D2, D3 and D2/3 receptor antagonists indicated that the dopamine D2 and D3 receptor antagonists increased survival, while the other agents did not [133]. This is an interesting result, as the clinical studies using antipsychotics with dopamine D2/D3 antagonism have not shown benefits (see above).…”
Section: Neurobiology Of Anmentioning
confidence: 99%